PELAKSANAAN URUSAN PEMERINTAHAN UMUM DALAM MEMBINA KERUKUNAN BERAGAMA OLEH PEMERINTAH KOTA BANDUNG - Novie Indrawati Sagita (Penamas, 2018)
Abstract Under Law No. 23 of 2014, mentioned that one of the government's business is general government affairs. The general government affairs is the authority of the president that organized by the head of the region as a leader of administrative work areas. One of the general government affairs is fostering inter-ethnic harmony, inter-religious, racial and other groups in order to achieve security and stability of local, regional, and national levels. Since the 2014 presidential elections, many dissatisfied group trying to disrupt the stability of the national government. They blew the issues of intolerance of religious differences, including in the city of Bandung. At the end of 2016, a Moslem organization intimidate Christians worship activities at Sabuga, Bandung. And then, there was an incident that organization known hacking attack against members of the FPI. Issues of religious difference that spread in the community and intolerant actions can potentially bring social conflict and disintegration. This study used a qualitative method. The analysis is done by integrating the primary data obtained by observation and interview, mass media, expert opinions, and other sources of relevant literature. Research results indicate that the Government of Bandung City quickly enough in addressing the issue of religious intolerance. The coordination and synergy among regional leaders who joined in ‘Forkopimda’ both in the city level and district level is very good to anticipate and prevent the symptoms of social conflict. Therefore, it is necessary for the effective working program of ‘Forkopimda’ by forming a task force. The task force is constantly monitoring the situation, security and social order, so when it is known there will be a plan of action that has potential of social conflict, the local government can overcome early on.